Body grammar and its meanings: an ethnography of the clinical context on language, and motor aphasia in a hospital in Mexico City - Taylor, Tomas Loza; Maya, Alfredo Paulo (Ciencia & Saude Coletiva, 2022)
This text is the result of an ethnographic research conducted in the neurological rehabilitation service at the Center for Mental and Neurological Health Care in Mexico City. This work focuses its problematic on elucidating how the body language of people with motor aphasia is reconstructed and what senses they generate. The analysis of the collected information led us to identify that language rehabilitation reconstructs a body grammar and uses the ability to narrate in order to restore language and communication. In this sense, we follow Goffman's notion of strip of activity, Csordas' embodiment and Bakhtin's polyphony, in order to understand the discursive construction of language that is introjected into the body and reproduced during clinical interaction. The employed methodology was an ethnography of the clinical context using narratives as a suitable tool to describe the meaning constructed between therapists and people affected with motor aphasia.
Keywords: Anthropology, Cultural; Aphasia, Broca; Hospitals; Humans; Linguistics; Mexico